2017
DOI: 10.1038/cddis.2017.176
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram/copper selectively eradicates AML leukemia stem cells in vitro and in vivo by simultaneous induction of ROS-JNK and inhibition of NF-κB and Nrf2

Abstract: Acute myeloid leukemia (AML) is a heterogeneous malignancy. Despite the advances in past decades, the clinical outcomes of AML patients remain poor. Leukemia stem cells (LSCs) is the major cause of the recurrence of AML even after aggressive treatment making, promoting development of LSC-targeted agents is an urgent clinical need. Although the antitumor activity of disulfiram (DS), an approved anti-alcoholism drug, has been demonstrated in multiple types of tumors including hematological malignancies such as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 48 publications
5
63
1
Order By: Relevance
“…6C) were used, namely the inflammatory stimulus interferon gamma (IFNg) and the aldehyde dehydrogenase inhibitor disulfiram (DS)(Amici et al, 2018;Xu et al, 2017). We confirmed that treatment with IFNg or DS enriched both Tet2 KO and WT populations for the differentiated cell state after 72 hours of exposure (Methods,Figure 4E, SupplementalFigure 6A-B).…”
supporting
confidence: 69%
“…6C) were used, namely the inflammatory stimulus interferon gamma (IFNg) and the aldehyde dehydrogenase inhibitor disulfiram (DS)(Amici et al, 2018;Xu et al, 2017). We confirmed that treatment with IFNg or DS enriched both Tet2 KO and WT populations for the differentiated cell state after 72 hours of exposure (Methods,Figure 4E, SupplementalFigure 6A-B).…”
supporting
confidence: 69%
“…NF-κB consists of a family of transcription factors, including p52, p50, c-rel, RelA (p65) and RelB, and is a key transcription factor, which mediates immune responses to inflammation and cell proliferation, and protects against UV radiation (25). Several studies have shown that the generation of ROS can subsequently activate NF-κB (26,27). The results of the present study showed that expression levels of the NF-κB p65 subunit were increased following exposure to cholesterol, indicating that cholesterol induced the accumulation of ROS in EA.hy926 cells (28) and then caused the upregulation of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that DSF/Cu induced NPL4 (an adapter of p97/VCP segregase) aggregation and induced a complex cellular phenotype, finally leading to cell death [11]. Moreover, DSF/Cu was reported to induce significant cell cycle arrest and apoptosis, cause the disturbance of the ROS balance, and activate the stress-related ROS-JNK pathway as well as downregulate the NF-E2-related factor-2 (Nrf2) and Nuclear factor-кB (NF-кB) pathways in some tumor cells [12][13][14]. In addition, the anticancer effect of DSF is also related to epigenetics [15].…”
Section: Introductionmentioning
confidence: 99%